Prevalence of Musculoskeletal Dysfunctions among Indian Pregnant Women. (6th January 2015) - Ramachandra, Preetha; Maiya, Arun G.; Kumar, Pratap; Kamath, Asha
Abstract : Background and Objectives . Pregnancy triggers a wide range of changes in a woman's body leading to various musculoskeletal dysfunctions. Most commonly reported musculoskeletal discomforts by pregnant women are low back pain and symphysis pubis pain. The culture and the environmental factors may influence the discomforts experienced by a pregnant woman. There is a dearth of literature in India, regarding the common musculoskeletal dysfunctions experienced by a pregnant woman, and hence this study. Method . A questionnaire to identify the musculoskeletal dysfunction was developed; content was validated and was translated to local languages through parallel back translation. 261 primiparous pregnant women participated in the study and filled the questionnaire in their native language. Results . Among the musculoskeletal dysfunctions reported by the pregnant women, 64.6% reported calf muscle cramps, 37.1% reported foot pain, and 33.7% experienced low back pain in their third trimester. In the second trimester, common musculoskeletal dysfunctions experienced by the women were that of calf pain (47.8%), low back pain (42%), and pelvic girdle pain (37%). Conclusion . Musculoskeletal dysfunctions and general discomforts very commonly affect the activities of daily living of pregnant women. Understanding the common discomforts during various trimesters of pregnancy will help to develop a comprehensive program for prevention and cure.